CyTOF protocol for immune monitoring of solid tumors from mouse models - Sarah M. Shin; Alexei Hernandez; Erin Coyne; Kabeer Munjal; Nicole E. Gross; Soren Charmsaz; Xuan Yuan; Hongqui Yang; Won Jin Ho (STAR Protocols, 2023)
Summary: Techniques for robust immune profiling of mouse tumor and blood are key to understanding immunological responses in mouse models of cancer. Here, we describe mass cytometry (cytometry by time-of-flight) procedures to facilitate high-parameter profiling of low-volume survival blood samples and end-of-study tumor samples. We employ live-cell barcoding systems to mark all cells from each tumor and blood to improve cost-effectiveness and minimize batch effects.For complete details on the use and execution of this protocol, please refer to Charmsaz et al. (2021).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.